2022
DOI: 10.1093/infdis/jiac174
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Dolutegravir Plasma Exposure Among Southern Africans With Human Immunodeficiency Virus

Abstract: Background Dolutegravir is a component of preferred antiretroviral therapy (ART) regimens. We characterised the pharmacogenetics of dolutegravir exposure following ART initiation in the ADVANCE trial in South Africa. Methods Genome-wide genotyping followed by imputation was performed. We developed a population pharmacokinetic model for dolutegravir using non-linear mixed-effects modelling. Linear regression models examined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Additionally, a recent study in adults from South Africa found that the rs2231137 SNP in ABCG2 had no effect on dolutegravir concentrations. 22 Thus, even in adults, the impact of rs2231137 on dolutegravir PK is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study in adults from South Africa found that the rs2231137 SNP in ABCG2 had no effect on dolutegravir concentrations. 22 Thus, even in adults, the impact of rs2231137 on dolutegravir PK is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Children from the United States comprised 21 (36%) of participants, with the remainder of the children being from countries in Africa, Thailand, and Brazil. The median (Q1-Q3) log 10 plasma HIV RNA was 4.79 (4.15-5.31) and the median (Q1-Q3) CD4 + lymphocyte percentage was 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Children had been on another antiretroviral regimen a median (Q1-Q3) of 2.8 (1.2-6.4) years before study entry.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Plasma dolutegravir concentrations were measured by liquid chromatography with mass tandem spectrometry detection using an AB SCIEX API 4000 instrument, in the Division of Clinical Pharmacology at the University of Cape Town as described elsewhere. 10 A population pharmacokinetic model was developed from the intensively sampled cohort using non-linear mixed-effects modelling. Individual 24-h dolutegravir area under the concentration-time curve (AUC 0-24h ) values were estimated from sparse samples using a post hoc Bayesian estimation method that accounted for participant characteristics.…”
Section: Pharmacokinetic Analysis and Modellingmentioning
confidence: 99%
“…While this was not significant after correcting for multiple testing, it lends support to the concept that UGT1A1 homozygous minor allele carriers of the UGT1A1 polymorphism rs887829 exhibited a 26% reduction in dolutegravir clearance compared to those homozygous for the major allele. 10 The rs929596 and rs887829 polymorphisms have been mapped to a UGT1A cluster located on Chromosome 2 that houses multiple protein-coding, and non-encoding, genes. 40 These polymorphisms were in moderate LD in this population (R 2 = .75), which suggests that their effects may not be entirely independent.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation